Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1128/mcb.24.1.362-376.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role for BRG1 in Cell Cycle Control and Tumor Suppression

Abstract: Human BRG1, a subunit of the Swi/Snf chromatin remodeling apparatus, has been implicated in regulation of cellular proliferation and is a candidate tumor suppressor. Reintroduction of BRG1 into a breast tumor cell line, ALAB, carrying a defined mutation in the BRG1 gene, induced growth arrest. Gene expression data revealed that the arrest may in part be accounted for by down-regulation of select E2F target genes such as cyclin E, but more dramatically, by up-regulation of mRNAs for the cyclin-dependent kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
141
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(160 citation statements)
references
References 61 publications
(86 reference statements)
16
141
2
1
Order By: Relevance
“…Several reports showed that BRG1 operates through regulation of these key cellular pathways (Strobeck et al, 2000;Lee et al, 2002;Hendricks et al, 2004;Kang et al, 2004). RB expression seemed to remain unaffected by BRG1 silencing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several reports showed that BRG1 operates through regulation of these key cellular pathways (Strobeck et al, 2000;Lee et al, 2002;Hendricks et al, 2004;Kang et al, 2004). RB expression seemed to remain unaffected by BRG1 silencing.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, our data suggest that BRG1 silencing altered the homeostasis of DNA repair pathway. In fact, the H2AX activation and the upregulation in the expression BRG1, RB and P53 crosstalk Several reports suggested that BRG1 binds to and regulates the retinoblastoma protein and the tumor suppressor protein p53 (Strobeck et al, 2000;Lee et al, 2002;Hendricks et al, 2004;Kang et al, 2004). These are master genes that control cell cycle arrest, differentiation, apoptosis and/or senescence (Felsani et al, 2006;Galderisi et al, 2006;Campisi and d'Adda di Fagagna, 2007;Oberdoerffer and Sinclair, 2007).…”
Section: Genes Involved In Dna Repairmentioning
confidence: 99%
See 2 more Smart Citations
“…Other more distantly related enzymes include human hBrm, Brg1 and the CHD family (CHD1-7). Of note, human hBrm and Brg1 are two candidate tumor suppressor genes that are implicated in repression of E2F target genes and induction of cell differentiation and senescence, through physical and functional interactions with the pRB protein (33,38,56,76,85,104,105,115,124,134,142). Since E2F target genes are incorporated into SAHF and formation of SAHF requires an intact pRB pathway (88,140), hBrm and/or Brg1 might be involved in SAHF assembly, perhaps through deposition of macroH2A.…”
Section: Incorporation Of Other Sahf Componentsmentioning
confidence: 99%